(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In recent years, digital technologies and artificial intelligence (AI) have begun to transform nutrition research and dietetics practice. This review examines how AI and digital tools are applied in dietary assessment, personalized planning and behaviour monitoring; how mobile apps and digital platforms support nutrition counselling; how machine-learning models predict nutrient intake and health outcomes; the ethical, privacy and equity concerns that arise; and future trends including AI-driven virtual dietitians and fully integrated nutrition-care ecosystems. Although promising, the deployment of these innovations must navigate issues of data quality, algorithmic bias, professional roles, user engagement and regulatory frameworks. Effective integration into dietetics will require interdisciplinary collaboration, transparent methods, and equitable access.